Advanced oxidation processes for wastewater reuse - removal of micropollutants - James, Christopher P. (Cranfield University, 2013)
The removal of micropollutants (MPs) from secondary municipal wastewater by an advanced oxidation process (AOP) based on UV irradiation combined with hydrogen peroxide (UV/H2O2) has been assessed through pilot-scale experiments incorporating microfiltration (MF) and reverse osmosis (RO). Tests employed low concentrations of a range of emerging contaminants of concern, and the water quality varied by blending of waters from different sources. Under optimum H2O2 and lamp power conditions, the process achieved >99% removal of N-nitrosodimethylamine (NDMA) and endocrine disrupting compounds (EDCs) from all waters. Pesticide removal, in particular metaldehyde, atrazine and 2, 4 5-T, was dependent on water transmittance (UVT), and levels of Total Organic Carbon (TOC) and other hydroxyl radical (HO.) scavengers. Chloroform, a trihalomethane (THM), was not readily degraded (<10% removal in either stream), as was TOC removal. Further analysis of metaldehyde removal identified UVT, reaction time, and H2O2 dose to be influential parameters in determining degradation as a function of UV dose. In comparison, the impact of H2O2 dose and UVT was negligible on NDMA degradation; removal increased from 89 to >98% on increasing the UV dose from 200 to 680 mJ cm-2 from the MF permeate. Nitrite by-products were observed at elevated levels, promoted by low pH and high UV doses. An operational cost assessment revealed energy consumption to account for 65% with lamp replacement contributing 25%. A comparison of three unit process sequences, based on MF, RO, AOP and activated carbon (AC), revealed MF-RO-AOP to be the most cost effective provided management of the RO concentrate stream incurs no significant cost. Results demonstrated AOPs to satisfactorily reduce levels of the more challenging recalcitrant MPs to meet stringent water quality standards for wastewater reuse, but that practical limitations exist and the cost penalty is significant.
Keywords: AOP; UV/H2O2; wastewater reuse; micropollutants; metaldehyde; NDMA